Code Mixing in Folk Songs: A Journey towards Linguistic Creativity - Bhetuwal, Kamali Kanta (KMC Research Journal, 2020)
Folk song is a true gift of culture. It is one of the traditional, intangible and indigenous pieces of the art of performing the melodious expression with the help of soft pipes that are forever invaluable cultural assets and musical property as well. In view of making a brief survey of the use of multiple languages in folk songs, different folk melodies have been selected randomly from seven provinces of Nepal where the folk melodies are more fertile. This paper aims at exploring the use of multiple languages in folk songs I, myself as a researcher in the field, encountered with in written and audio- or video-recorded form. Therefore, the main source of relevant data includes me and other written and audio or video documents of folk songs I found. As a multicultural country, Nepal is rich in terms of its folk songs. In this paper, I analyze how folk song can be a creative space where linguistic boundaries are challenged and new language practices are invented. Taking of folk songs as a social and cultural identity, I examine how folk song embraces local diversity and redefines the use of language a creative tool for public.